Sejarah Lokal dan Desentralisasi Pendidikan di Indonesia - Noviyana Sari; Serly Fatma Yanti (UIN Imam Bonjol Padang, 2022)
The diversity of the Indonesian is not just aspects of culture, language, ethnicity, but also the process of social change of society and history in each region has differences. History is not a blank and rigid space, departing from an autocritic of the History Education curriculum which has some weakness, this paper focuses on the study of the lack of local historical content in the curriculum of historical education and attempts to initiated discourses to be an alternative to enrich the content of history education with local history without ruling out Indonesia's national history. The local history can be a consideration, in addition to touching the localities and being closer to the students, local history learning can also be a means to preserve local wisdom and indigenous cultures in each region. Decentralization of education as a delegation of authority to local authorities provides opportunities for the application of local history in the curriculum of history subjects. Education policy and design of local history education curriculum can be devolved by regional authorities, cultural and historical communities, and Musyawarah Guru Mata Pelajaran dan Kelompok Kerja Guru (MGMP / KKG).